Study of the addition of overflow doors as flood control (study of ameroro dam case) - Anwar Sanusi; Ratna Musa; Ali Mallombasi; Mas’ud SAR (Sean Institute, 2024)
Floods are a natural phenomenon that can cause damage to people, property and lives. Floods become a cause for concern when losses are incurred, as rivers usually take up their channel space before they reach human habitation. Floods can be caused by a variety of factors, including the state of the rain-catchment area, the length and intensity of the rainfall, soil cover, topographical conditions and the drainage network's storage capacity. One of the structures that can be used for flood control and prevention is a dam. This study aimed to analyze the return flood discharge and flood tracing through the spillway with the addition of 2 spillway gates at the Ameroro Dam. The study was carried out by analyzing secondary data and primary data obtained through data collection and field surveys. The data analysis stage determines the size of the Design Watershed Hydrograph from the design rainfall calculation using the Snyder Unit Hydrograph method in HEC-HMS 4.11 software. The return period flood discharge in the Ameroro dam for the return period Q 2th = 224.26 m3/s, Q 5th = 270.26 m3/s, Q 10th = 301.73 m3/s, Q 25th = 340.71 m3/s, Q 50th = 369.65 m3 /s, Q 100th = 398.34 m3/s, Q 1000th 493.21 m3/s, and Q PMF = 1222.66 m3/s. When two spillway gates are used to trace floodwaters through the spillway, the outflow discharge is less or the flood is reduced when there are no spillway gates used. Therefore, it is safer for the structure of the dam body and more effective to reduce floods at the Ameroro Dam to use two spillway gates.